The effectiveness of an ERP implementation in a South African logistics company - Shepherd, John (My University, 2014)
This research report chronicles an ERP system implementation at a large logistics company in order to evaluate the perceptions of success of the implementation amongst the various stakeholders based on their differing views and objectives for the implementation. Critical success factors are used as the basis on which to analyse users’ and implementers’ perceptions of success of the implementation. The research reveals that different stakeholder perceptions and experiences of the implementation differ substantially. It also shows that the view of which critical success factors were most critical differs substantially and that the effectiveness of the deployment thereof is questionable. The research suggests that the deployment of critical success factors be actively monitored by management and the project team. The research also shows that management would be advised to encourage a mentality amongst the project team and the eventual end users the system of “if you want it to work then you need to make it work”.
MBA thesis
Keywords: Enterprise resource planning